Organizational Readiness And Innovation Capabilities in a Context Of Manufacturing Company: Will Leadership Skills Mediates? - Anita Maharani; Widuri Supriatna; Linda Linda; Fitri Yanni (Kusuma Negara Business School, 2021)
This study aimed to see the link between organizational readiness, leadership skills, and innovation capabilities. The context of this study is in manufacturing because the urgency in the manufacturing industry drives it to have the readiness to face business challenges, then understood as the term organizational readiness. The manufacturing ability to find new ways of doing business processes and researchers suspect these two things requires contributions from individuals in leadership skills. The method used in this research is a quantitative approach. These research samples are 105 respondents from manufacturing. We collect the data by distributing questionnaires with online forms. All process results obtained using SmartPLS to see the reliability value through composite reliability and average variance values ​​explained, validity through discriminant validity, and the bootstrapping process to see whether the proposed hypothesis is supported or not. The results indicated that leadership skills do not contribute either as a moderator or mediating role.